EVALUASI PROGRAM PENDIDIKAN SISTEM GANDA BERDASARKAN STAKE COUNTENANCE MODEL (Universitas Negeri Semarang, 2012)
Tujuan Penelitian ini adalah mengetahui tingkat keterlaksanaan Program Pendidikan Sistem Ganda (PSG) pada tahapan 1) masukan (antecedents), 2) proses (transactions), 3) hasil (output). Subyek Penelitian meliputi Wakil Kepala Sekolah bidang kurikulum, Wakil Kepala Sekolah bidang Humas DuDi, Wakil Kepala Sekolah bidang Sarpras, Wakil Kepala Sekolah Bidang Siswa, Instruktur/Pembimbing DuDi, dan Peserta didik yang sudah melaksanakan PSG. Teknik pengambilan data melalui 4 cara yaitu : wawancara, dokumentasi, observasi, dan kuesioner. Hasil penelitian pada tahap 1) masukan (antecedents) meliputi a) pada sistem PPDB menggunakan POS, kriteria kelulusan menggunakan nilai UN dan tes wawancara, belum menggunakan tes akademik, b) Kurikulum Tingkat Satuan Pendidikan (KTSP), 46 jam per minggu, jam praktek 16 jam; c) administrasi PSG baik dan lengkap; d) ketersediaan mitra kerja/DuDi mencukupi; belum semua DuDi melaksanakan Mou, e) kualifikasi guru praktek S.1, belum semua memiliki sertifikat kompetensi, 2) proses (transaction) meliputi a) pelaksanaan PSG selama 2 bulan (400 jam), b) kualifikasi pembimbing PSG S.1, c) kualifikasi instruktur/pembimbing DuDi masih SLTA, d) kriteria penilaian dari pembimbing DuDi mencakup aspek kognitif, sikap, dan ketrampilan, belum ada indikator yang jelas, e) keterlibatan pembimbing DuDi secara periodik dan sesuai dengan job pekerjaan, 3) tahap hasil (output) meliputi a) nilai hasil belajar/praktek kerja dari aspek kognitif, sikap, dan ketrampilan. rata-rata minimal 7.5, belum menggunakan indikator yang rinci, b) nilai hasil ujian praktek akhir semester rata-rata minimal 7.5. The declaration of Central Java Government as a Vocation Province impacts the role of vocational schools as the centre of education and training, the centre of science and technology development, as well as the centre of production and marketing. Dual System of Education (DSE) was initiated by the former Ministry of Education and Culture in 1994 Prof. Dr. Ing Wardiman Djojonegoro. It was a system that links and matches the interest between education and in-dustry.The objectives of this research are to examine the implementation level of Dual System of Education in phase 1) antecedents consisted of system/criteria of student admission, current curriculum, school facilities, DSE administration, industry partnership and teacher qualification; 2) transactions consisted of schedule, supervisor qualification, instructor qualification, assessment criteria, and structural involvement; 3) output consisted of student achievement in the form of assessment from the industry, student achievement after the implementation of Dual System of Education in the final competency test.The subject of the research was the Vice Principle of Curriculum, the Vice Principle of External Af fair, the Vice Principle of Facility and Infrastructure, the Vice Principle of Student Affair, Instructor/Supervisor, and students of Dual System of Education. The data were gathered from interview, documentation, observation and questionnaire.The results in phase: 1) antecedents are: a) in PPDB system using POS, the criteria for graduation use national examination score and interview result, not academic test, b) School Based Curriculu, 46 hours per week, 16 hours for vocational practice, c) well-managed administration, d) sufficient partnership availability, some partners have not implemented Mou yet, e) bachelor teacher qualification, some teachers have not had competence certificates; 2) transactions are: a) DSE implementation in 2 months (400 hours), b) DSE supervisor qualification, c) instructor qualifi-cation, d) assessment criteria with cognitive, af fective and skill aspect with unobvious indicator, e) supervisor involvement periodically according to the job description; 3) outputs are: a) result of vocational study and practice from cognitive, affective and skill aspect. The mean was 7.5 with undetailed indicator, b) result of final vocational practice. The mean was 7.5 with unobvious indicator.